Iceland : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Iceland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Iceland's 2008 Article IV Consultation shows that the long expansion is coming to an end, exposing the economy's overstretched private sector balance sheets, large macroeconomic imbalances, and high dependence on foreign financing. With external liquidity constraints binding, economic activity is expected to slow significantly from unsustainably high levels, inflation to remain well above target, and the current account to narrow. Uncertainty surrounding the outlook is unusually large, dominated by significant downside risks, both external and domestic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet